MG-AL SAPPHIRINE- AND CA-AL HIBONITE-BEARING GRANULITE XENOLITHS FROM THE CHYULU HILLS VOLCANIC FIELD, KENYA - Ulianov A.; Kalt A. (My University, 2006)
Basanites of the Chyulu Hills (Kenya Rift) contain mafic Mg-Al and Ca-Al granulite xenoliths. Their protoliths are interpreted as troctolitic cumulates; however, the original mineral assemblages were almost completely transformed by subsolidus reactions. Mg-Al granulites contain the minerals spinel, sapphirine, sillimanite, plagioclase, corundum, clinopyroxene, orthopyroxene and garnet, whereas Ca-Al granulites are characterized by hibonite, spinel, sapphirine, mullite, sillimanite, plagioclase, quartz, clinopyroxene, corundum, and garnet. In the Mg-Al granulites, the first generation of orthopyroxene and some spinel may be of igneous origin. In the Ca-Al granulites, hibonite (and possibly some spinel) are the earliest, possibly igneous, minerals in the crystallization sequence. Most pyroxene, spinel and corundum in Mg-Al and Ca-Al granulites formed by subsolidus reactions. The qualitative P-T path derived from metamorphic reactions corresponds to subsolidus cooling, probably accompanied, or followed by, compression. Final equilibration was achieved at T≈600-740°C and P <8 kbar, in the stability field of sillimanite. The early coexistence of corundum and pyroxenes (± spinel), as well as the association of sillimanite and sapphirine with clinopyroxene and the presence of hibonite, makes both types of granulite rare. The Ca-Al hibonite-bearing granulites are unique. Both types enlarge the spectrum of known Ca-Al-Mg-rich granulites worldwide. © 2006 Oxford University Press.
Keywords: CORUNDUM; GRANULITE XENOLITHS; HIBONITE; KENYA RIFT; SAPPHIRINE